National Geographic Almanac 2020 : Trending Topics, Big Ideas in Science, Photos, Maps, Facts & More - Published by National Geographic (Washington DC National Geographic, 2020)
"The latest dynamic annual for the 21st century, featuring high-energy pages packed with facts, photos, infographics, time lines, and maps that capture today's world. Perfect for ages 12 to 112. An almanac like no other, this book offers everything you need to know about the world in 2020-from science and nature to history, world cultures, and the environment. Filled with exquisite National Geographic photography, informative infographics, illustrated time lines, and authoritative maps, this striking new edition will celebrate the 50th anniversary of Earth Day with practical tips for improving your own sustainability habits. The book begins with trending topics in science, technology, and culture, then moves into fascinating chapters on travel, exploration, earth and space, biology, culture, and history. Recurring features include inspiring quotes, revealing facts, photos from National Geographic's Instagram, and a Quizmaster trivia feature. With new discoveries on every page, this cutting-edge book brings you the world, no matter what your age."--Publisher's website.
Include Color Illustrations, Maps and Index
Keywords: Almanacs -- Almanacs, American -- Curiosities and wonders -- Earth Day